Self-care of a woman with AIDS: a model of nursing care - Barroso, Léa LMMB; Carvalho, Carolina CMLC; Araújo, Thelma TLA; Galvão, Marli MTGG (Online Brazilian Journal of Nursing, 2006)
Context: Aids impairs the functioning of the body, causing a deviation of health that requires the patient himself as an active agent of self-care. Objective: The objective of the present study was to apply the nursing process based on the self-care theory of Orem to a woman infected with HIV/Aids. Method: This was a case study conducted on the ward of a tertiary hospital in November 2004. Results: The behaviors observed indicated the absence of self-care practice, such as failure to attend the visits and abandonment of treatment, in addition to changes in life style after the onset of the disease, such as difficulty to sleep, despondency, anxiety, restlessness and lack of motivation for daily activities. The nursing diagnoses and interventions were elaborated according to the deviations from health. Conclusion: We conclude that the application of the theoretical model of Orem was adequate to promote the practice of self-care by providing support for the execution of self-care activities.